Evaluation of remodeling and regeneration of electrospun PCL/fibrin vascular grafts in vivo - Zhao, Liang (Mater Sci Eng C Mater Biol Appl, 2021)
The success of artificial vascular graft in the host to obtain functional tissue regeneration and remodeling is a great challenge in the field of small diameter tissue engineering blood vessels. In our previous work, poly(ε-caprolactone) (PCL)/fibrin vascular grafts were fabricated by electrospinning. It was proved that the PCL/fibrin vascular graft was a suitable small diameter tissue engineering vascular scaffold with good biomechanical properties and cell compatibility. Here we mainly examined the performance of PCL/fibrin vascular graft in vivo. The graft showed randomly arranged nanofiber structure, excellent mechanical strength, higher compliance and degradation properties. At 9 months after implantation in the rat abdominal aorta, the graft induced the regeneration of neoarteries, and promoted ECM deposition and rapid endothelialization. More importantly, the PCL/fibrin vascular graft showed more microvessels density and fewer calcification areas at 3 months, which was beneficial to improve cell infiltration and proliferation. Moreover, the ratio of M2/M1macrophage in PCL/fibrin graft had a higher expression level and the secretion amount of pro-inflammatory cytokines started to increase, and then decreased to similar to the native artery. Thus, the electrospun PCL/fibrin tubular vascular graft had great potential to become a new type of artificial blood vessel scaffold that can be implanted in vivo for long term.